2022
DOI: 10.3390/foods11030490
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Physicochemical, Microbiological, and Organoleptic Characteristics of Sugar- and Fat-Free Ice Cream from Buffalo Milk

Abstract: Ice cream is a popular dessert product across the world. Structure, body, taste, and odor properties are created by adding non-milk ingredients and milk ingredients. The main aim of the study is to decrease the caloric value of ice cream by using sugar and fat replacements. Ice cream treatments were investigated based on microstructural, chemical, physical, microbiological, sensory, and calorific values. Four different ice creams were used (control ice cream (SC1), ice cream with stevia (SC2), ice cream with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, animal studies have hinted at a negative relationship between AS and T2DM [40][41][42]. In contrast, thorough safety assessments have confirmed their safety [43], and reputable organizations have vouched for their safety [7]. Nevertheless, innate limitations in observational studies make it difficult to fully negate the impact of unobserved confounding variables and reverse causality.…”
Section: Plos Onementioning
confidence: 99%
“…However, animal studies have hinted at a negative relationship between AS and T2DM [40][41][42]. In contrast, thorough safety assessments have confirmed their safety [43], and reputable organizations have vouched for their safety [7]. Nevertheless, innate limitations in observational studies make it difficult to fully negate the impact of unobserved confounding variables and reverse causality.…”
Section: Plos Onementioning
confidence: 99%
“…The reason for its popularity lies in its nutritional value and refreshing perception during consumption [4][5][6][7][8]. According to Research and Markets [9], the average consumption of ice cream across Europe is 6.20 L per/capita each year, while the average American eats about 10 kg of ice cream per year [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that buffalo milk may offer several advantages over other milk, including higher protein content, superior emulsion property, and defense against pathogens due to immunomodulatory proteins [15][16][17][18][19]. In terms of food technology, buffalo milk is a promising source of innovative products because it contains high fat and protein, which makes it ideal for processing [9,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%